(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s ((3eMjj GdOjf Hf TjN eMeO GdMGaX GdcdSj GdMfajs)
(3ChdgG (B:s
(3ShQI Gdcga ecjI GrdnMreoO pdnqdpg GnqdpPj nCrfnRnd nYdi nYrHpOpg GrdpcJGnH jYfj GdbQBf, QJH GSJMbGb GdMeO Ydi EfRGdg JfHjgkG Ydi Cfg CYXe fYeGFg, hPdc dCfg GdgGOj Edi eG ajg ceGd GdYHGO hGdOGYj Edi eG Hg jfJXe UdGM GdeYGT hGdeYGO nhndre njrLnYrd ndog pYnhLkG TjFkGs
(3BNQgG (B:s
(3penf GrdpLnqfpI nhGdnqfGpS HjGf d GrdnhrShGpS, Ch ddPj Ch eJYdb H ojnhrSphoS Cj jhShS aj UOhQge ef LgI GdpLnqfnI hGdfGS hbjd HjGf ddnqfGpS Ydi Cf GdeQGO Hg eG jYe GdKbdjf, hajg JYSa EdG Cf jQGO Hg GdfGSj cbhdg (B: (3njrhne njrOoY GdnqOGpY aEf fSjGf Mb Gddg JYGdi jYe GdKbdjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 110s
(3eYLe GdeDdajf (B2 / 266s
(3cTa GdXfhf (B1 / 186s
(3TPQGJ GdPgH (B5 / 392s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs